Diffusion of oxytocin in water: a molecular dynamics study - Acharya, Khimananda; Koirala, Rajendra Prasad; Pantha, Nurapati (BIBECHANA, 2021)
Classical molecular dynamics simulation is performed to estimate the diffusion coefficient of oxytocin in the water at different temperatures, 288 K, 300 K, 313 K, 323 K, using Groningen Machine for Chemical Simulations (GROMOCS). The simulation is carried out using GROMOS43A1 force field and extended simple point charge (SPC/E), water model. The stability of the system is evaluated from the energy profile of potential and kinetic energy, which assures a well equilibrated molecular system. The self-diffusion coefficient of oxytocin and water is obtained from Einstein’s relation and the binary diffusion coefficient is obtained from Darken’s relation. As temperature increases, the diffusion coefficient also increases as per expectation. The diffusion coefficients of water from the present calculations agree well with the previously reported values, within the 10% of deviation. Furthermore, the activation energy has been studied using Arrhenius Plot.BIBECHANA 18 (1) (2021) 108-117